Positive Urine Morphine Test in a Chinese Patient Receiving Methadone Maintenance Treatment After Eating Hot Pot: A Case Report - Ma, Jun; He, Yafei; Zeng, Kuan; Liu, Xuebing (Frontiers in Psychiatry, 2020)
Poppy shells contain opioids. If the shells are added to food, urine morphine test of the patients in MMT can be positive. A 44-year-old male patient, who had been receiving methadone maintenance treatment (MMT) for more than two years with very good treatment adherence, was found to have positive urine morphine test in a routine clinical compliance monitoring. However, the patient denied the use of any opioids recently. Coincidently, his four family members (without history of heroin abuse) were all found to be positive in urine morphine test. Consider that they ate hot pot together one day before the test, we speculated that it was because the hot pot with poppy shell adding, a popular but illegal spicy in China. This unusual phenomenon is worthy of clinical attention when managing patients at MMT clinics.